Thermodynamics : an engineering approach - Cengel, Yunus A.; Boles, Michael A. (McGraw-Hill, 2011)
Covers the basic principles of thermodynamics while presenting real-world engineering examples so students get a feel for how thermodynamics is applied in engineering practice. This book helps students develop an intuitive understanding of thermodynamics by emphasizing the physics and physical arguments